Ameliorative effect of Aconite aqueous extract on diarrhea is associated with modulation of the gut microbiota and bile acid metabolism - Zhang, Dandan; Cheng, Hao; Zhang, Yuxi; Zhou, Yaochuan; Wu, Jing; Liu, Juan; Feng, Wuwen; Peng, Cheng (Frontiers in Pharmacology, 2023)
Introduction: Aconite is a traditional Chinese medicine (TCM) that is widely used to treat diarrhea for thousands of years. However, it is not clear whether the antidiarrheal role of Aconite aqueous extract (AA) is associated with regulating gut microbiota and bile acids (BAs) metabolism. The experiment was conducted to confirm whether AA can exert its antidiarrheal effects by regulating gut microbiota and BA metabolism. Methods: The therapeutic effect of AA on diarrhea was measured by body weight, fecal water content, diarrhea scores, intestinal propulsion rate, colonic pathology, and colonic immunohistochemistry. In addition, 16S rRNA high-throughput sequencing was used to analyze the effect of AA on gut microbiota, and targeted metabolomics was used for analyzing the effect of AA on BAs metabolism. Results: The results showed that AA could reduce fecal water content and diarrhea score, inhibit intestinal propulsion rate and colon pathological changes, and increase AQP3 and AQP4 in the colon. In addition, AA can regulate gut microbiota, including increasing gut microbiota richness (Ace and Chao index), altering gut microbiota community structure (PCA, PCoA, and NMDS), increasing the relative abundance of norank_f_Muribaculaceae, Ruminococcus, Lachnospiraceae_NK4A136_group, Prevotellaceae_UCG-001, and norank_f_norank_o_Clostridia_UCG-014, and decreasing the relative abundance of Escherichia-Shigella, unclassified_f_Ruminococcaceae, Ruminococcus_torques_group, and Parasutterella. More importantly, AA can significantly increase fecal primary BAs TCA, and secondary BAs DCA, LCA, GDCA, dehydro-LCA, and 12-keto-LCA to restore BAs’ homeostasis. Also, AA increased the ratio of DCA/CA, DCA/TCA, and LCA/CDCA, and decreased the ratio of TLCA/LCA, GLCA/LCA, and TUDCA/UDCA. Conclusion: The antidiarrheal role of AA is associated with the restoration of gut microbiota and BA metabolism-related homeostasis. This study provides insights into the application of AA and the treatment of diarrhea.